PENGARUH GERAKAN LITERASI SEKOLAH TERHADAP MINAT MEMBACA SISWA KELAS V SD INPRES 3/77 WATU KECAMATAN BAREBBO KABUPATEN BONE - Kadir A, Abd; Mujahidah; Paramitha, Andi (MACCA : Science-Edu Journal, 2025)
This research is a quantitative research with a correlational design using a regression model aimed at determining the significant influence of the School Literacy Movement on the reading interest of fifth-grade students at SD Inpres 3/77 Watu, Barebbo District, Bone Regency. The population consists of 34 fifth-grade students, selected using a total sampling technique. Data collection was conducted using a questionnaire to obtain information on the School Literacy Movement and students' reading interest. The research instrument consisted of 20 validated questions for the School Literacy Movement and 20 validated questions for students' reading interest. Data analysis techniques included descriptive statistical analysis and inferential statistical analysis. Based on the analysis results, the obtained significance value is 0.000, which means that there is a significant influence of the School Literacy Movement on the Reading Interest of Fifth Grade Students at SD Inpres 3/77 Watu, Barebbo District, Bone Regency.